Appearance can be Deceptive- A Case Report on Central Venous Line Complication - Ali, Mohammod; Khan, Fauzia; Sarker, Sudhakar; Bashar, Abul Hasan Muhammad; Chowdhury, Abdul Wadud (Cardiovascular Journal, 2021)
Central venous (CV) lines are widely used for anything from rapid fluid resuscitation, to drug administration, to parenteral nutrition, and even for administering hemodialysis. Central lines come in different sizes, types, and sites of administration. Sometimes their use can be associated with complications as well. Our patient is an 85 years old hypertensive, diabetic female presenting with post COVID fibrosis with aspiration pneumonia with septic shock. After admissions in ICU, CV line was inserted through right sub-clavian venous route for administration of essential medications including inotropes. However, forceful backflow of blood was noticed after insertion of CV line raising the suspicion of arterial insertion. It was later confirmed by CXR, ABG and duplex arterial study. Taking appropriate precautions, we were able to remove the CV line safely without any complications. Sometimes minor and easy things like CV like insertion can become life threatening. But with proper knowledge and planning we can overcome any complications. Cardiovasc j 2021; 14(1): 73-75